Boron nitride nanotube‐functionalised myoblast/microfibre constructs: a nanotech‐assisted tissue‐engineered platform for muscle stimulation. (4th March 2014) - Danti, Serena; Ciofani, Gianni; Pertici, Gianni; Moscato, Stefania; D'Alessandro, Delfo; Ciabatti, Elena; Chiellini, Federica; D'Acunto, Mario; Mattoli, Virgilio; Berrettini, Stefano
Abstract In this communication, we introduce boron nitride nanotube (BNNT)‐functionalised muscle cell/microfibre mesh constructs, obtained via tissue engineering, as a three‐dimensional (3D) platform to study a wireless stimulation system for electrically responsive cells and tissues. Our stimulation strategy exploits the piezoelectric behaviour of some classes of ceramic nanoparticles, such as BNNTs, able to polarize under mechanical stress, e.g. using low‐frequency ultrasound (US). In the microfibre scaffolds, C2C12 myoblasts were able to differentiate into viable myotubes and to internalize BNNTs, also upon US irradiation, so as to obtain a nanotech‐assisted 3D in vitro model. We then tested our stimulatory system on 2D and 3D cellular models by investigating the expression of connexin 43 (Cx43), as a molecule involved in cell crosstalk and mechanotransduction, and myosin, as a myogenic differentiation marker. Cx43 gene expression revealed a marked model dependency. In control samples (without US and/or BNNTs), Cx43 was upregulated under 2D culture conditions (10.78 ± 1.05‐fold difference). Interactions with BNNTs increased Cx43 expression in 3D samples. Cx43 mRNA dropped in 2D under the 'BNNTs + US' regimen, while it was best enhanced in 3D samples (3.58 ± 1.05 vs 13.74 ± 1.42‐fold difference, p = 0.0001). At the protein level, the maximal expressions of Cx43 and myosin were detected in the 3D model. In contrast with the 3D model, in 2D cultures, BNNTs and US exerted a synergistic depletive effect upon myosin synthesis. These findings indicate that model dimensionality and stimulatory regimens can strongly affect the responses of signalling and differentiation molecules, proving the importance of developing proper in vitro platforms for biological modelling. Copyright © 2014 John Wiley & Sons, Ltd.